术前超声心动图检查异常与非心脏手术患者术后主要不良心脏事件的关系：一项巢式病例对照研究 - Chun-jing, LI; GUO, Chao; Bo-jie, WANG; Dong-liang, MU; Dong-xin, WANG (Jie fang jun yi xue za zhi, 2018)
Objective To investigate the relationship between preoperative abnormal transthoracic echocardiogram (TTE) and postoperative major adverse cardiac events (MACE) in patients undergoing non-cardiac surgery. Methods This study was a nested case control study. Patients who underwent elective non-cardiac surgery in Peking University First Hospital from November 15, 2012 to January 15, 2013 were enrolled. We screened patients who received preoperative TTE examination from electrical medical record. The primary outcome of this study was the incidence of postoperative MACEs. The patients were divided into MACE group and control group depending on if they suffered MACE. For each patient in MACE group, 4 patients without MACE events were selected for control group in term of two criteria: same revised cardiac risk index and same type of surgery. Related perioperative data were collected. Multivariate logistic analysis was used for screening potential risk factors related to MACE. Results During the study period, a tota